Legal Protection of Personal Data in Online Loan Transactions according to the Consumer Protection Law - Ahmad Yunianto; Yuniar Rahmatiar; Muhamad Abas (Journal Equity of Law and Governance, 2024)
Online loans that make it easy to get funding turn out to have a negative effect. In some cases, it can be found that there are debtors who choose to end their lives because they are not mentally strong in facing the threat accompanied by the spread of personal data. Lack of caution in filling out the terms and conditions submitted makes the chances of personal data leakage even greater. For this reason, legal protection is needed for debtors in terms of personal data. The purpose of the research is to find out the implementation of personal data rules in online loan transactions linked to the UUPK, to know the legal protection of debtors against personal data that is leaked without the knowledge of the debtor and what legal remedies can be taken by debtors in the misuse of personal data. The method uses a normative juridical approach, with secondary data in the form of data obtained based on literature studies and supporting data. There are still collection actions carried out by one of the online loan application services by distributing the debtor's personal data to several contacts of fellow debtors either through SMS or email short messages. This is contrary to the UUPK and also POJK 22/2023 Article 62 paragraph (2) letter c which explains that collection officers are not allowed to collect from parties other than Consumers.